Prophylactic CMV therapy does not improve three‐yr patient and graft survival compared to preemptive therapy. (25th November 2015) - Werzowa, Johannes; Schwaiger, Benedikt; Hecking, Manfred; Strassl, Robert; Schmaldienst, Sabine; Böhmig, Georg A.; Genser, Bernd; Säemann, Marcus D.
Abstract: Despite increasing evidence in favor of prophylactic valganciclovir treatment in kidney transplant recipients for the prevention of cytomegalovirus (CMV) infection, the impact of preemptive vs. prophylactic treatment on long‐term clinical outcomes is unclear. In this retrospective study, 187 kidney transplant recipients with serologic intermediate‐risk constellation (recipient CMV IgG positive) received either preemptive or prophylactic treatment with valganciclovir. Patient survival (primary endpoint), graft survival, viremia rates, and other CMV‐related outcomes were analyzed. Prophylactic therapy reduced the rates for CMV viremia during the first year (hazard ratio: 0.48, 95% confidence interval [CI] 0.30–0.75; p < 0.001). There was a trend for higher three‐yr patient mortality in the prophylactic group (hazard ratio: 5.08, 95% CI 0.62–41.3; p = 0.091), and the rate of graft loss was not reduced (hazard ratio: 0.93, 95% CI 0.32–2.68; p = 0.894). Estimated glomerular filtration rate over three yr was on average 6.8 mL/min/1.73 m 2 lower in the prophylactic group (95% CI −11.68 to −1.81; p = 0.007) using a multivariate random effects model but showed more improvement over time. Prophylactic valganciclovir treatment reduced the rate of CMV infections during the first year post‐transplant but no effects of prophylactic treatment on patient and graft survival or kidney function over three yr were observed.